THE SIMULTANEOUS QUANTIFICATION OF RIFAMPICIN AND ISONIAZID IN PATIENTS WITH TUBERCULOSIS APPLIED TO VOLUMETRIC ABSORPTIVE MICROSAMPLING DEVICES USING HIGH-PERFORMANCE LIQUID CHROMATOGRAPHY - RENDATI, HEMA NOVITA; HARAHAP, YAHDIANA; RAHMAYANTI (International Journal of Applied Pharmaceutics, 2024)
Objective: Rifampicin and isoniazid are the main tuberculosis treatment regimens requiring blood level measurement to optimize the treatment process. This study aims to analyze rifampicin and isoniazid quantitatively in volumetric absorptive microsampling (VAMS) prepared from a small volume of TB patients using HPLC. Methods: Analytes on the VAMS tip were extracted using 1000 ml of acetonitrile containing 10 µg/ml of cilostazol as an internal standard. Analytical separation was performed on the C-18 column at 40 ℃ with a mobile phase mixture of 50 mmol ammonium acetate buffer pH 5.0-acetonitrile-methanol (40:30:30), flow rate 0.5 ml/min. The analysis was carried out with the calibration curve over a range of 1.0–30 µg/ml for rifampicin and 0.4-20 µg/ml for isoniazid. Results: Analyte analysis in 21 patients showed that the measured value of rifampicin was 3.39–16.77 µg/ml, and isoniazid was 2.63–10.43 µg/ml at 2 h post-dose. 52.38% of patients had low blood concentrations in at least one of the drugs, 28.57% of the patients were in the therapeutic range, and 23.81% had a high blood concentration of isoniazid alone. Conclusion: The concentration of rifampicin and isoniazid in 21 tuberculosis patients varied. Dose adjustment is needed because most patients had low blood concentrations of one of the drugs, and a limited number had a high blood isoniazid concentration alone. Only some patients simultaneously had plasma concentrations within the target range of the drugs. This method was valid and reliably utilized for therapeutic drug monitoring of antituberculosis.